Altered cytoskeleton dynamics in patient-derived iPSC-based model of PCDH19 clustering epilepsy - Borghi, Rossella; Petrini, Stefania; Apollonio, Valentina; Trivisano, Marina; Specchio, Nicola; Moreno, Sandra; Bertini, Enrico; Tartaglia, Marco; Compagnucci, Claudia (Frontiers in Cell and Developmental Biology, 2025)
Protocadherin 19 (PCDH19) is an adhesion molecule involved in cell-cell interaction whose mutations cause a drug-resistant form of epilepsy, named PCDH19-Clustering Epilepsy (PCDH19-CE, MIM 300088). The mechanism by which altered PCDH19 function drive pathogenesis is not yet fully understood. Our previous work showed that PCDH19 dysfunction is associated with altered orientation of the mitotic spindle and accelerated neurogenesis, suggesting a contribution of altered cytoskeleton organization in PCDH19-CE pathogenesis in the control of cell division and differentiation. Here, we evaluate the consequences of altered PCDH19 function on microfilaments and microtubules organization, using a disease model obtained from patient-derived induced pluripotent stem cells. We show that iPSC-derived cortical neurons are characterized by altered cytoskeletal dynamics, suggesting that this protocadherin has a role in modulating stability of MFs and MTs. Consistently, the levels of acetylated-tubulin, which is related with stable MTs, are significantly increased in cortical neurons derived from the patient’s iPSCs compared to control cells, supporting the idea that the altered dynamics of the MTs depends on their increased stability. Finally, performing live-imaging experiments using fluorescence recovery after photobleaching and by monitoring GFP-tagged end binding protein 3 (EB3) “comets,” we observe an impairment of the plus-end polymerization speed in PCDH19-mutated cortical neurons, therefore confirming the impaired MT dynamics. In addition to altering the mitotic spindle formation, the present data unveil that PCDH19 dysfunction leads to altered cytoskeletal rearrangement, providing therapeutic targets and pharmacological options to treat this disorder.